2009
DOI: 10.1136/bjo.2008.150151
|View full text |Cite|
|
Sign up to set email alerts
|

Late-onset retinal macular degeneration: clinical insights into an inherited retinal degeneration

Abstract: Raised awareness of L-ORMD should lead to earlier diagnosis and improved care for patients. New antivascular endothelial growth factor treatment may provide a new possibility for management. A deeper insight into molecular and genetic mechanisms of L-ORMD may suggest avenues to explore new treatments of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(102 citation statements)
references
References 46 publications
3
96
0
1
Order By: Relevance
“…Late-onset retinal macular degeneration (L-ORMD) is a fully penetrant autosomal dominant disorder characterized by bilateral loss of vision, abnormal dark-adaption, drusen-like yellow spots in the fundus, choroidal neovascularization, retinal atrophy and long anteriorly inserted lens zonules (Borooah et al, 2009; Jacobson et al, 2001; Kuntz et al, 1996; Milam et al, 2000). L-ORMD is caused by a single S163R missense mutation in the globular C1q domain of the C1q and tumor necrosis factor-related protein 5 (C1QTNF5) (Hayward et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Late-onset retinal macular degeneration (L-ORMD) is a fully penetrant autosomal dominant disorder characterized by bilateral loss of vision, abnormal dark-adaption, drusen-like yellow spots in the fundus, choroidal neovascularization, retinal atrophy and long anteriorly inserted lens zonules (Borooah et al, 2009; Jacobson et al, 2001; Kuntz et al, 1996; Milam et al, 2000). L-ORMD is caused by a single S163R missense mutation in the globular C1q domain of the C1q and tumor necrosis factor-related protein 5 (C1QTNF5) (Hayward et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Dominante familiäre Drusen treten auch als Symptom bei der late-onset retinal macular degeneration (L-ORMD) auf. Sie ist durch Komplikationen wie subretinale Neovaskularisation und periphere Netzhautveränderungen gekennzeichnet [13].…”
Section: Familiäre Drusenunclassified
“…Patients are also predisposed to choroidal neovascularisation, usually by the sixth decade. 4 If untreated, the natural history of the lesions is poor. 1 To date, only laser photocoagulation of lesions in three eyes has been reported, with poor results.…”
Section: Case Reportmentioning
confidence: 99%
“…It has been reported that the Perkins tonometer can underestimate IOP by 0.6-1.5 mm Hg compared with the Goldmann tonometer. [2][3][4][5] If an underestimation by the Perkins tonometer occurred in this study, IOP values at night may have been underestimated.…”
mentioning
confidence: 99%